A Simulated Policy towards Green Public Transportation in a Metropolitan in Indonesia - Pujiati, Amin; Murniawaty, Indri; Nihayah, Dyah Maya; Muarrifah, Innal; Damayanti, Nadia (International Journal of Energy Economics and Policy, 2022)
The need for mode of transportation is proportional with urban population growth. The dependence of people using private transportation causes many problems. In addition to congestion, it can create environmental problems such as air quality deterioration and pollution in the cities. Learning to be in this research is the process of individual learning to move from private transportation to public transportation. The purpose of this study is to predict and opportunities for private decision using the public transportation toward green transportation in Semarang city. This research is designed using a quantitative approach. Respondents in this study were workers. Data collection methods with questionnaires. The samples are collected using proportional sampling technique. Data are analyzed with binary logistic regression. The results showed that the accessibility and tariff variables are significantly influence to predict private decision for using public transportation as an effort toward green transportation. Based on the policy simulation, the opportunity of using public transportation will be higher if the distance is closer and reachable. It will be getting lower if the tariff is raised when the other variables are constant. Therefore, to influence private decisions using the public transportation, the government must be oriented towards reachable distance and tariff.